Education in Vietnam, 1945-1991 - Phạm, Minh Hạc (Ministry of education and training of Vietnam, 1994)
This book introduce about Vietnam: sketches of history, geography, nationmality, population. Education reforms. General education in Vietnam. The system of middle technical schools and vocational schools. Higher education in Vietnam...